The practicality of popular scientific books of the diversity of Macrozoobenthos in the Sungai Puting - Rara Ramadanti; Danang Biyatmoko; Muhammad Zaini (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2023)
Teaching materials based on local potential are teaching materials that contain material or materials that are local in nature, and have ideas that can be understood and are closely related to the management of natural resources and the environment where teaching materials can help improve critical thinking skills. One of them is the application of local potential-based learning resources developed in this teaching material, namely popular scientific books (BIP). This study aims to examine the practicality of the contents, practical expectations and actual practicality of the developed BIP macrozoobenthos diversity. The method used refers to the formative evaluation design from Tessmer. The results of the research based on the readability test for the practicality test of the contents yielded 91.67% with very practical criteria, and student responses to the practicality of expectations obtained results of 93.33% and 95.83% on actual practicality with very practical criteria, and based on the implementation of the BIP that was developed on the implementation of expectations and actual implementation got a result of 85.19% in a very good category to be used as enrichment material for Animal Ecology courses and to improve students' critical thinking skills.Abstrak Bahan ajar berbasis potensi lokal merupakan bahan ajar yang berisi materi atau bahan yang bersifat lokal, dan memiliki gagasan-gagasan yang dapat dipahami dan berkaitan erat dengan pengelolaan sumber daya alam dan lingkungan yang mana bahan ajar dapat membantu meningkatkan keterampilan berpikir kritis. Salah satunya penerapan sumber belajar berbasis potensi lokal yang dikembangkan dalam bahan ajar ini ialah buku ilmiah popular (BIP). Penelitian ini bertujuan untuk menguji kepraktisan isi, kepraktisan harapan dan kepraktisan aktual dari BIP keanekaragaman makrozoobentos yang dikembangkan. Metode yang digunakan adalah mengacu pada desain evaluasi formatif dari Tessmer. Hasil penelitian berdasarkan uji keterbacaan untuk uji kepraktisan isi mendapatkan hasil 91,67% dengan kriteria sangat praktis, dan respon mahasiswa pada kepraktisan harapan mendapatkan hasil sebesar 93,33% dan 95,83% pada kepraktisan aktual dengan kriteria sangat praktis, dan berdasarkan keterlaksanaan BIP yang dikembangkan pada keterlaksanaan harapan dan keterlaksanaan aktual mendapatkan hasil 85,19% dengan kategori sangat baik untuk digunakan sebagai materi pengayaan mata kuliah Ekologi Hewan serta dapat meningkatkan keterampilan berpikir kritis mahasiswa.